Studying the Relationship between some Biokinematic Variables and some Physical Measurements with the Level of Achievement in 25-meter Freestyle Swimming - Dhiaa Zaki Ibraheem; Nawaf Owaid Abood; Falah Taha Hammo (Indonesian Journal of Physical Education and Sport Science)
Study purpose. Swimming experienced significant growth and achievement in the late twentieth century and early second millennium, marked by the creation of advanced records. This progress is due to rigorous training, practical experience, and the utilization of modern scientific techniques and applied sciences such as biomechanics. This study aims to evaluate several bio-kinematic variables, physical measurements, and completion times in 25-meter freestyle swimming.